2017
DOI: 10.1080/10245332.2017.1365458
|View full text |Cite
|
Sign up to set email alerts
|

Can biomarkers of coagulation, platelet activation, and inflammation predict mortality in patients with hematological malignancies?

Abstract: Some biomarkers of coagulation and inflammation showed statistically significant associations with plasma cell dyscrasias mortality (vWF and IL-6) and lymphoproliferative disorders mortality (Antithrombin) and potentially could be used as prognostic markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…72 A meta-analysis examining the prognostic effect of circulating fibrinogen in solid tumors showed a positive correlation between pretreatment fibrinogen levels and poorer survival (hazard ratio=1.51). 73 Conflicting results came from studies on hematologic cancers, [74][75][76] but overall patients with elevated baseline plasma fibrinogen levels had a significantly poorer clinical outcome.…”
Section: Cancermentioning
confidence: 99%
“…72 A meta-analysis examining the prognostic effect of circulating fibrinogen in solid tumors showed a positive correlation between pretreatment fibrinogen levels and poorer survival (hazard ratio=1.51). 73 Conflicting results came from studies on hematologic cancers, [74][75][76] but overall patients with elevated baseline plasma fibrinogen levels had a significantly poorer clinical outcome.…”
Section: Cancermentioning
confidence: 99%
“…Elmoamly S and colleagues measured inflammatory markers in a group of 171 patients with haematological malignancies. 84 The results indicated that the platelet activation marker von Willebrand Factor (vWF) was statistically related with the mortality of lymphoproliferative diseases, implying that vWF could be used as a prognostic marker. In addition, Shi L et al found that the platelet activation index is a potential marker for predicting gemcitabine/cisplatin (GP) resistance in the treatment of advanced and metastatic non-small cell lung cancer (NSCLC).…”
Section: Activated Platelets Can Participate In Tumour Formation and mentioning
confidence: 99%
“…Elmoamly S and colleagues measured inflammatory markers in a group of 171 patients with haematological malignancies. 84 The results indicated that the platelet activation marker von Willebrand Factor (vWF) was statistically related with the mortality of lymphoproliferative diseases, implying that vWF could be used as…”
Section: Osteosarcomamentioning
confidence: 99%
“…Sixty patients (35%) died during the follow-up period. Some biomarkers of coagulation and inflammation showed significant associations with the mortality of patients with plasma cell dyscrasia (vWF and IL-6) and lymphoproliferative disorders (antithrombin) and could potentially be used as prognostic markers [53]. …”
Section: Discussionmentioning
confidence: 99%